Electroacupuncture Intervention Improves Post-Stroke Dysphagia by Modulating NMDAR1 and GABABR1 - Wang, Jinjin; Ma, Qinqin; Li, Fang; Yuan, Zhengzhong; Li, Haiyan; Fu, Wenbin (Current neurovascular research, 2025)
Post-stroke dysphagia (PSD) is a common complication after acute stroke. It can be effectively alleviated by electroacupuncture (EA) stimulation at the Baihui acupoint; however, the underlying mechanism remains unclear. Male ICR mice were used, and the suture occlusion method was employed to establish the middle cerebral artery occlusion (MCAO) mouse model. EA stimulation was applied to the Baihui acupoint for intervention. After treatment, the survival rate of the mice was assessed. Subsequently, a water swallow test was conducted to evaluate the degree of dysphagia in the mice. Additionally, neurological function was assessed through Garcia scoring and measurement of serum Ca2+-Mg2+-ATPase activity. Fur-thermore, MRI was utilized to evaluate the therapeutic effects of EA on cerebral infarction and edema rates. Then, the antioxidant activity of the EA intervention was assessed by measuring indicators of oxida-tive damage. Finally, the expressions of gamma- aminobutyric acid type B receptor subunit 1 (GAB-ABR1), N-methyl-D-aspartate receptor 1 (NMDAR1) were detected through WB, RT-qPCR, and immu-nofluorescence. EA intervention effectively increased the survival rate of MCAO mice and alleviated their dysphagia. Additionally, the impaired neurological function of the mice was improved, and cerebral infarction and edema rates were reduced. Furthermore, EA alleviated oxidative stress in mice, reduced damage to neurons in the nucleus ambiguus, and upregulated GABABR1 while downregulating NMDAR1. Although we suggested that EA may exert therapeutic activity for PSD by maintaining the balance of NMDAR1 and GABABR1, this conclusion still requires further experimental validation. EA stimulation of the Baihui acupoint was effective in treating PSD, which was related to its ability to improve damaged neurons, upregulate GABABR1, and downregulate NMDAR1. These findings provided a new insight into the mechanisms of EA treatment for PSD and serve as a theoretical basis for future clinical research.